PELATIHAN DAN PENDAMPINGAN KKN PPM PRODUKSI KERAJINAN MOZAIK KACA SEBAGAI KOMODITI EKSPOR POTENSIAL DAN SOUVENIR KOTA WISATA YOGYAKARTA - Maryanto, Al.; Rosana, Dadan; Maryati, - (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2016)
This program aims to (1) conduct a workshop to enhance the skills ofstudents as a strategic objective in designing and making glass mosaic crafts as a precious work of art; (2) involve students in skills enhancement of productive age youth as key strategic objectives in designing and crafting glass mosaic; (3) build networks in the form of a group of small business production and open up access to markets through partnerships with Cooperatives and SMEs (called UKMK) in developing youth as a pioneering institute of Cooperative and SMEs. Some methods were used in the impowerment such as training, workshops and mentoring. Overall method involves the students and youth in the target areas of the program. The results that have been obtained are (1) the skills of students in designing and making crafts glass mosaic as a valuable work of art increases; (2) There is a growing youth skills of youth age as the main strategic objectives in designing and crafting glass mosaic; (3) Formed cooperation in marketing products through exhibitions of Kulon Progo Regency Development. The local government provides full support for the implementation of the program